2007
DOI: 10.1177/0003319707304943
|View full text |Cite
|
Sign up to set email alerts
|

Increased High Sensitive CRP Level and Its Significance in Pathogenesis of Slow Coronary Flow

Abstract: Previous studies have suggested that microvascular abnormalities cause slow coronary flow (SCF). The role of inflammation has not been investigated, to date. The purpose of this study was to determine the role of inflammation in pathogenesis of SCF. The study included 32 patients with angiographically proven SCF (mean age 49 +/-9 years) (group I) and 30 subjects with normal coronary flow (mean age 48 +/-8 years) (group II). Blood samples were collected for high sensitive CRP (hs-CRP) measurements. Thrombolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 23 publications
3
39
0
Order By: Relevance
“…Even though SCF has been related to inflammatory process, a recent study, comparing SCF patients with normal coronary angiograms also found similar CRP levels (35), which is in line several studies (24,36). On the contrary, there are studies that report increased CRP levels in patients with SCF (37,38). These conflicting results might stem from heterogeneity of recruited patients and/or clinical state of the SCF phenomenon.…”
Section: Discussionmentioning
confidence: 97%
“…Even though SCF has been related to inflammatory process, a recent study, comparing SCF patients with normal coronary angiograms also found similar CRP levels (35), which is in line several studies (24,36). On the contrary, there are studies that report increased CRP levels in patients with SCF (37,38). These conflicting results might stem from heterogeneity of recruited patients and/or clinical state of the SCF phenomenon.…”
Section: Discussionmentioning
confidence: 97%
“…Li et al (8) showed that plasma levels of inflammatory factors, CRP and IL-6 in patients with SCF were found to be significantly higher than those of control subjects. Barutçu et al (9) have found that serum hs-CRP concentration was increased in patients with SCF as compared to control group. On the other hand, Yazıcı et al (20) found that plasma CRP levels were not elevated in patients with SCF when compared with controls.…”
Section: Discussionmentioning
confidence: 95%
“…Several mechanisms have been proposed for etiology of SCF, including microvascular and endothelial dysfunction, small-vessel disease and diffuse atherosclerosis (1)(2)(3)(4). It has also been proposed that inflammation is another important etiologic factor (5)(6)(7)(8)(9)(10). Its etiopathogenesis is not still clear.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of CSF has not been clearly identified yet, although multiple abnormalities including inflammation, oxidative stress, endothelial dysfunction, vasculitis, platelet function disorder and atherothrombosis have been reported [19]. Increased cardiovascular morbidity and mortality have been demonstrated in patients with CSF in previous studies [8].…”
Section: Discussionmentioning
confidence: 99%